South Africa and Malaysia: identity and history in South-South relations - Haron, Muhammed (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2008)
The focus of this thesis is on the bilateral relationship between South Africa and Malaysia. The thesis appropriates 'critical theory,' and as a flexible theoretical tool, and, as an open-ended, loose frame in order to give voice to the marginalized and voiceless from the South. The thesis thus looks at the politico-economic ties that have been developed and brings into view the socio-cultural relations that had been established between the peoples of the two sovereign nation-states during the apartheid and post-apartheid eras respectively. The basic purpose of this study was fivefold: (a) to contribute to the extant literature that concentrates on South Africa's relations with Malaysia, (b) to examine the relationship at political and economic ties in some detail, (c) to demonstrate that apart from the afore-mentioned bonds IR specialists should also take into account the socio-cultural dimensions of international relations, (d) to bring to light the nation-state's limitations when discussing the role of non-state actors and considering the contributions of other factors such as globalization, and (e) to stimulate further research on bilateral and multilateral relations in the South "“ particularly between South Africa and other states in Asia and Latin America - that would assist to better understand the past, present and perhaps the future.
Keywords: Critical theory; South Africa -- Foreign relations -- Malaysia; Malaysia -- Foreign relations -- South Africa; South Africa -- Politics and government -- History; Malaysia -- Politics and government -- History; South Africa -- Politics and government; Malaysia -- Politics and government; South Africa -- Social conditions -- History; Malaysia -- Social conditions -- History; South Africa -- Economic conditions; Malaysia -- Economic conditions